AI-powered education: Revolutionizing teaching and learning through artificial intelligence in Jordan - Almahasees, Zakaryia; Al-Harahsheh, Ahmad; Albudairi, Yousef (Research Journal in Advanced Humanities, 2024)
This paper examines the integration of AI-powered tools in educational settings and focuses on teacher satisfaction, perceived effectiveness, and problems with adopting AI. It used a mixed methodology; it combined a quantitative structured survey with closed-ended and five open-ended questions to check the educators’ views on this issue.-. The survey was created online using Google Forms. It was disseminated online, such as Facebook, LinkedIn, and Twitter. The survey received 300 respondents; the closed questions were statistically analyzed, while the open-ended questions were thematically analyzed. The results reflect a notable discrepancy in the satisfaction level; however, almost half of the respondents are dissatisfied with the integration of AI, while two-thirds recognize the benefits of its use in improving efficiency in teaching and personalized learning. The paper also unearths significant challenges, such as a steep learning curve and ethical issues like bias and privacy concerns. However, most educators believe in AI's possibilities, especially changing the whole phase of education through personalization and automation. Consequently, the debate emphasizes the issues of continuous training, transparency, and participation in the argument of AI in Education. The paper concludes with a final plea: balance the advanced integration of AI with inclusiveness, transparency, and alignment with educational goals to realize the maximal potential of these tools for revolutionizing teaching and learning.